The Role of Connexin-43 in the Inflammatory Process: A New Potential Therapy to Influence Keratitis - Chu-Yang Xu; Wen-Song Zhang; Hong Zhang; Yan Cao; Hong-Yan Zhou (Journal of Ophthalmology)
The studies outlined in this review highlight the relationship between inflammatory signaling molecules and connexin-43 (Cx43). Gap junction (GJ) channels and hemichannels (HCs) participate in the metabolic activity between intra- and extracellular space. Some ions and small molecules are exchanged from cell to cell or cell to extracellular space to affect the process of inflammation via GJ. We analyzed the effects of signaling molecules, such as innate immunity messengers, transcription factors, LPS, cytokine, inflammatory chemokines, and MMPs, on Cx43 expression during the inflammatory process. At the same time, we found that these signaling molecules play a critical role in the pathogenesis of keratitis. Thus, we assessed the function of Cx43 during inflammatory corneal disease. Corneal healing plays an essential role in the late stage of keratitis. We found that Cx43 is involved in wound healing. Studies have shown that the decrease of Cx43 can decrease the time of healing. We also report several Cx43 mimic peptides which can inhibit the activity of Cx43 Hc to mediate the releasing of adenosine triphosphate (ATP), which may in turn influence the inflammatory process.